Effects of Organizational Coordination Dimensions on Employee Performance: Evidence from an Indonesian Local Government - Ade Setiadi (International Journal of Science Education and Cultural Studies, 2024)
Employee performance is a key determinant of organizational effectiveness in the public sector, where the successful implementation of government programs depends on effective coordination among organizational units. However, the empirical evidence of the effect of organizational coordination on employee performance in Indonesian local government institutions is still limited. This study aims to find out the effect of organizational coordination on employee performance at the Department of Education and Culture of Indramayu Regency, Indonesia. The approach was quantitative explanatory method, and data were collected through a census survey of all 54 employees of the organization. Data were collected using a structured questionnaire. The data were analyzed by path analysis following instrument validity and reliability testing and the MSI transformation. The results reveal that organizational coordination has significant effect on employee performance, and the proposed model explains 52.6% of the variation in employee performance. Among the coordination dimensions studied, authority, work guidelines, forums and conferences had a positive effect on employee performance showing the importance of clear responsibilities, standardised procedures and continuous communication in supporting the effectiveness of the organization. These findings highlight that enhanced coordination mechanisms can lead to enhanced employee performance and public service delivery. The research extends the empirical evidence on organizational coordination in local government agencies and offers practical recommendations for public managers interested in enhancing organizational performance through improved coordination practices.